2022
DOI: 10.7160/eriesj.2022.150306
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Effectiveness Measurements and Bias Publication of Literature Results Study: A Cooperative Learning Models on Mathematics Learning Outcomes of Vocational School Students in Indonesia

Abstract: This meta-analysis intends to determine the impact of cooperative learning model research findings on the mathematics learning outcomes of Indonesian vocational high school students. Based on moderator variables, such as grade level and student sample size, identify efficacy and publication bias measures. Data from descriptive analysis, which included the mean, standard deviation, and sample size, were collected from 21 research projects based on applying the cooperative learning model in the experimental grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Several studies that used meta-analysis found that the learning model improved learning outcomes and math skills. They found that cooperative learning models improve math learning outcomes [38], [39], [40] and math skills [41], [42, [43]. However, the six research studies used descriptive data comparing the results of the two learnings in the experimental and control classes using standard deviation, mean data, and sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies that used meta-analysis found that the learning model improved learning outcomes and math skills. They found that cooperative learning models improve math learning outcomes [38], [39], [40] and math skills [41], [42, [43]. However, the six research studies used descriptive data comparing the results of the two learnings in the experimental and control classes using standard deviation, mean data, and sample size.…”
Section: Introductionmentioning
confidence: 99%